2021
DOI: 10.1080/17461391.2021.1943716
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evolution of cartilage abnormalities and osteophytes in the fingers of elite sport climbers: A cross‐sectional 10‐year follow‐up study

Abstract: The sequelae of high mechanical stress to the proximal interphalangeal (PIP) and distal interphalangeal (DIP) joints of the fingers in elite sport climbers and its contribution to the development of osteoarthritis are still relatively unknown. The purpose of this study was to investigate the evolution of cartilage abnormalities of the PIP and DIP joints, as well as the progress of osteophytes, in the fingers of elite sport climbers with a minimum of 25 years of climbing history over the time period of the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 27 publications
(32 reference statements)
0
9
0
1
Order By: Relevance
“…With further climbing years, the cartilage, however, decreased over a decade but was still thicker as compared with non-climbing controls. Furthermore, a clear correlation to pain could not be found [ 13 ], and the question of whether these findings were early signs of osteoarthritis or just mechano-adaptations could not be conclusively clarified. In contrast, several other studies have found clear signs of osteoarthritis in the fingers of climbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With further climbing years, the cartilage, however, decreased over a decade but was still thicker as compared with non-climbing controls. Furthermore, a clear correlation to pain could not be found [ 13 ], and the question of whether these findings were early signs of osteoarthritis or just mechano-adaptations could not be conclusively clarified. In contrast, several other studies have found clear signs of osteoarthritis in the fingers of climbers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a height- and weight-matched 40-year-old non-climbing male surgeon was evaluated for a direct comparison of the presented pictures. We waivered a perfect age matched control, because no significant increases in size (osteophytes, bones, cartilage, pulley, flexor tendons and palmar plates) over a 10-year follow-up period could be found in the fingers of non-climbers in previously published studies [ 11 , 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is associated with a high incidence of acute injuries, such as finger pulley rupture, which represents the most common climbing injury ( 9 ). Concerning joint tissue adaptation as a response to repetitive stress and loading, cartilage alterations and osteoarthritis (OA) development in the finger joints have been examined in several studies but an association between climbing activity and early OA development could not be shown ( 10 – 13 ). Young top athletes may develop tissue adaptations such as an increase in cartilage thickness and cortical thickness ( 13 , 14 ) at an early stage of their career.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning joint tissue adaptation as a response to repetitive stress and loading, cartilage alterations and osteoarthritis (OA) development in the finger joints have been examined in several studies but an association between climbing activity and early OA development could not be shown ( 10 – 13 ). Young top athletes may develop tissue adaptations such as an increase in cartilage thickness and cortical thickness ( 13 , 14 ) at an early stage of their career. Studies by Pastor et al focussed on long-term climbing athletes performing at a high level and investigated a possible connection between cartilage and cortical thickness, osteophyte development and pain symptoms in follow-up studies ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation